UPAYA MENINGKATKAN KEMAMPUAN KOGNITIF PENGENALAN LAMBANG BILANGAN MELALUI MEDIA KARTU ANGKA DI TK AL-IHSAN UJUNGBATU KABUPATEN ROKAN HULU - Marliana marliana (JURNAL PENDIDIKAN ROKANIA, 2018)
This research is a research action (action research). Subjects in this study amounted to 17 people yan. The focus of this research is how to improve the cognitive ability of the recognition of the number symbol through the number card media in TK AL-Ihsan Ujungbatu. This study aims to improve the cognitive ability of the introduction of number symbols through the media of card numbers in TK AL-Ihsan Ujungbatu. The use of numerical card media on learning the introduction of the number symbols proved to improve student learning outcomes and students' cognitive abilities from the first meeting of the first cycle of 53% which requires guidance and reduced to 12% at the first meeting of cycle II.